Process of capital/process of labour: cryptotheologies of judgement, time and nature in the dominant economics/economy - Piotrowski, Mateusz Aleksander (2017)
The main argument of the thesis is that the dominant form of economics and correlative form of economy - despite its apparently secular character - contains an inherently cryptotheological dimension. A theological analysis exposes the dominant economics/economy as an instance of ‘law’ understood (after saint Paul Franz Kafka and Walter Benjamin) as a process engaging the subject into an infinite endeavour of justifying oneself by one’s own works. Within the framework of the dominant economics/economy, all labour is formalised as steaming from lack and unrest and the final end of action is formalised as non-action. Therefore peace can only be conceptualised as a perfect lack of action (viz. death). As a consequence death itself becomes the final end, that cannot be achieved as long as the subject lives.